Exploring the relationship of digital information sources and medication adherence. (June 2019) - Arbuckle, Cody; Tomaszewski, Daniel; Brown, Lawrence; Schommer, Jon; Morisky, Donald; Parlett-Pelleriti, Chelsea; Linstead, Erik
Abstract: We present a retrospective analysis of data collected in the United States from the 2015 National Consumer Survey on the Medication Experience and Pharmacists' Role in order to model the relationship between health information sources and medication adherence and perception. Our results indicate that while the digital age has presented prescription users with many non-traditional alternatives for health information, the use of digital content has a significant negative correlation with pharmaceutical adherence and attitudes toward medication. These findings along with previous research suggest that in order to fully realize the potential benefits of the digital age in regards to patient health, positive patient-provider discussions regarding information found online, efforts to improve general health literacy and improvements in the quality and accuracy of the information found are key. Given that higher reliance on digital content is correlated with younger age, the analysis suggests that proactive measures should be taken to educate younger prescription users about the merits and pitfalls of information seeking techniques as they pertain to health literacy.